Start with why : how great leaders inspire everyone to take action [book club bag] - Sinek, Simon (Portfolio, 2011)
Why are some people and organizations more innovative, more influential, and moer profitable than others? Why do some command greater loyalty from customers and employees alike? Even among the successful, why are so few able to repeat their success over and over? In studying the leaders who've had the greatest influence in the world, Simon Sinek discovered that they all think, act, and communicate in the exact same way -- and it's the complete opposite of what everyone else does. Sinek calls this powerful idea The Golden Circle, and it provides a framework upon which organizations can be built, movements can be lead, and people can be inspired. Any organization can explain what it does; some can explain how they do it; but very few can clearly articulate why. Why does your organization exist? Why does it do the things it does? Why do customers really buy from one company or another? Why are people loyal to some leaders, but not others? Drawing on a wide range of real-life stories, Sinek weaves together a clear vision of what it truly takes to lead and inspire..."--Jacket.